THE IMPLEMENTATION OF BRATA ŚIVALATRI VALUES FOR HUMAN BEING IN THE COVID-19 ERA - Ni Nyoman Sudiani; Adison Adrianus Sihombing; I Wayan Saklit; Kadek Hemamalini (UHN I Gusti Bagus Sugriwa Denpasar, 2022)
This article aims to find out the values of Brata Śivalatri and their implementation during the Covid-19 outbreak which is studied through a qualitative approaching. When Śivalatri, Dewa Śiva performs yoga, the people who do tapa brata will recieve blessing from Dewa Śiva. The form of grace is believed to be gaining progress and living in Śiva loka after death as experienced by Lubdaka. Every Śivalatri time the people do brata as a form of their faith and devotion. The various of brata that should be done are: no eating and drinking (Upavasa), not talking (Mauna Brata), and not sleeping (Jagra Brata). Each brata has it owns religious and ethical values. So far, Brata Śivalatri has been done because apart from spiritual cleansing, it also has a positive infact on worldly life, which can be implemented in real life, especially during the covid -19 outbreak. The implementation of Brata Śivalatri in society is being able to maintain the health; peace; and increase alertness and awareness. It happened because doing the Brata Śivalatri can control lust.